Multiculturalism in the Namesake by Jhumpa Lahiri & the Bamboo Stalk by Saud Alanousi: Exploring Multiculturalism in Contemporary English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Multiculturalism entails the acceptance of disparity found in cultural diversity and ethnic qualities regarding sustenance, dialect, dispositions, conventions or cultural legacies. Multiculturalism isn't about minorities yet is about the best possible managing the connection between different cultural networks. Multiculturalism empowers a cultural or religious network to allow the statement of various cultures without segregation.Writing in English has a worldwide application. Late English writing is progressively combining its multicultural establishment in light of the fact that the scholars over the world are expounding on their culture. This paper talks about multiculturalism in the namesake by Jhumpa Lahiri and the bamboo stalk by Saud Alanousi.